The Effect of Three Months of Aerobic Training on Response Preparation in Older Adults - Renaud, Mélanie; Maquestiaux, François; Joncas, Steve; Kergoat, Marie-Jeanne; Bherer, Louis (Frontiers in Aging Neuroscience, 2010)
This study assessed the effects of an aerobic training program on reaction time tasks that manipulated preparatory intervals to produce temporal preparation effects using short (1, 3, 5s) and long (5, 7, 9s) preparatory intervals. Older adults were assigned to either a three-month aerobic training group or to a control group. Individuals in the training group participated in an aerobic training program of three 60-minute sessions per week. The control group did not receive any training. Results indicated that 12 weeks of aerobic training induced a significant improvement in cardiorespiratory capacity (VO2max estimate). All participants who completed the aerobic program showed improvement after training in the choice RT task, along with enhanced preparation, such that they maintained preparation over time more efficiently after the training program. Moreover, enhanced ability to use the short preparatory intervals was observed but only in lower fit individuals. Results of the present study suggest that improving aerobic fitness may enhance attentional control mechanisms in older adults.